A Clinical Update on Vasoactive Medication in the Management of Cardiogenic Shock. Issue 16 (February 2022) - Shankar, Aditi; Gurumurthy, Gayathri; Sridharan, Lakshmi; Gupta, Divya; Nicholson, William J; Jaber, Wissam A; Vallabhajosyula, Saraschandra
This is a focused review looking at the pharmacological support in cardiogenic shock. There are a plethora of data evaluating vasopressors and inotropes in septic shock, but the data are limited for cardiogenic shock. This review article describes in detail the pathophysiology of cardiogenic shock, the mechanism of action of different vasopressors and inotropes emphasizing their indications and potential side effects. This review article incorporates the currently used specific risk-prediction models in cardiogenic shock as well as integrates data from many trials on the use of vasopressors and inotropes. Lastly, this review seeks to discuss the future direction for vasoactive medications in cardiogenic shock.